Genome-Wide Association Study for Indicator Traits of Sexual Precocity in Nellore Cattle - Irano, Natalia [UNESP]; Ferreira de Camargo, Gregorio Miguel [UNESP]; Costa, Raphael Bermal [UNESP]; Nascimento Terakado, Ana Paula [UNESP]; Braga Magalhaes, Ana Fabricia [UNESP]; Oliveira Silva, Rafael Medeiros de [UNESP]; Dias, Marina Mortati [UNESP]; Bignardi, Annaiza Braga; Baldi, Fernando [UNESP]; Carvalheiro, Roberto [UNESP]; Oliveira, Henrique Nunes de [UNESP]; Albuquerque, Lucia Galvao de [UNESP] (Public Library Science, 2016)
The objective of this study was to perform a genome-wide association study (GWAS) to detect chromosome regions associated with indicator traits of sexual precocity in Nellore cattle. Data from Nellore animals belonging to farms which participate in the DeltaGen (R) and Paint (R) animal breeding programs, were used. The traits used in this study were the occurrence of early pregnancy (EP) and scrotal circumference (SC). Data from 72,675 females and 83,911 males with phenotypes were used; of these, 1,770 females and 1,680 males were genotyped. The SNP effects were estimated with a single-step procedure (WssGBLUP) and the observed phenotypes were used as dependent variables. All animals with available genotypes and phenotypes, in addition to those with only phenotypic information, were used. A single-trait animal model was applied to predict breeding values and the solutions of SNP effects were obtained from these breeding values. The results of GWAS are reported as the proportion of variance explained by windows with 150 adjacent SNPs. The 10 windows that explained the highest proportion of variance were identified. The results of this study indicate the polygenic nature of EP and SC, demonstrating that the indicator traits of sexual precocity studied here are probably controlled by many genes, including some of moderate effect. The 10 windows with large effects obtained for EP are located on chromosomes 5, 6, 7, 14, 18, 21 and 27, and together explained 7.91% of the total genetic variance. For SC, these windows are located on chromosomes 4, 8, 11, 13, 14, 19, 22 and 23, explaining 6.78% of total variance. GWAS permitted to identify chromosome regions associated with EP and SC. The identification of these regions contributes to a better understanding and evaluation of these traits, and permits to indicate candidate genes for future investigation of causal mutations.